PEMETAAN POTENSI DAN DAMPAK EKONOMI MASYARAKAT DI KAWASAN PERTAMBANGAN BUKIT TUMPANG PITU BANYUWANGI - Sukriyah Kustanti Moerad; Endang Susilowati; Windiani Windiani (JURNAL SOSIAL HUMANIORA (JSH), 2016)
Bukit Tumpang Pitu is located in Sumber Agung village, district of Pesanggaran, Banyuwangi region. There ara seven hills around Bukit Tumpang and it contains gold minning resourses. Since 2000, this area had been minning  by local community with conventional method. On 20008, Local Government of Banyuwangi gave access for doing explaration in this area  to Indo Multi Niaga corporation (IMN ltd). And this made the minners segemented into two types, i.e: a conventional and  labor corporation minner. This research intends to make a map of local potention in this minner area and to see that there is an economic impact for the community in minning area. The method used is a grounded research, by using survey method, observation and interview with respondent through sample-questioner. This research wants to show that  there are many economic pontentions to earn in this area. Since minner area, many people will come to this place. Besides the economic function, this area  have tourism destination. It is Red Island beach and reside at near to the  minner area.